PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT DOM PIZZA INDONESIA CABANG BINTARO - Pieter Katanga Jani, Patrick; Apriansyah, Muger (Journal of Research and Publication Innovation, 2024)
"The Influence of Work Discipline and Work Motivation on Employee Performance at PT Dom Pizza Indonesia”. The purpose of this study was to determine the effect of work discipline and work motivation on employee performance at PT. Dom Pizza either partially or simultaneously. This type of research used is Quantitative. The population in this study are employees of PT Dom Pizza Indonesia. The sampling technique used saturated sampling technique and the sample in this study was 50 respondents. Data collection technique is a questionnaire, while data analysis using validity test, reliability test, classical assumption test, simple and multiple linear regression analysis, analysis of the coefficient of determination and hypothesis testing. Based on the results of the study using SPSS 25, the t test results obtained tcount for Work Discipline is smaller than the ttable value of 1.678 or (1.107 <1.678) with a significant value of 0.274 > 0.05. So it can be concluded that partially Work Discipline has a positive but not significant effect on Employee Performance. This means that Ho is accepted and Ha is rejected. The tcount value of Work Motivation is greater than ttable 1.678 or (3.869 > 1.678) with a significant value of 0.000 <0.05. So it can be concluded that partially Work Motivation has a positive and significant effect on Employee Performance. This means that Ho is rejected and Ha is accepted. For the F test, an Fcount value of 17.620 is obtained and a significant value is 0.000 so that it can be concluded that Work Discipline and Work Motivation simultaneously affect Employee Performance as evidenced by the Fcount value ¬17.620 > Ftable 3.195 and a significant value of 0.000 <0.05, it can be concluded that Ho is rejected and Ha ¬accepted. The results of multiple linear analysis obtained Y = 5.470 + 0.134X1 + 0.732X2